Interactions With Plant Defences Isolate Sympatric Populations of an Herbivorous Mite - Villacis-Perez, Ernesto; Alba, Juan Manuel; Cotte, Julien; van Loon, Zeno; Breeuwer, Johannes A. J.; Van Leeuwen, Thomas (Frontiers in Ecology and Evolution, 2022)
Host plant specialization can promote evolutionary divergence between herbivore populations associated with different plant species. While the mechanisms by which specialist species exploit their hosts have been studied widely across taxa, less is known about the mechanisms that allow intraspecific variants to arise and to be maintained across spatial and temporal scales. To understand whether adaptations to plant defences against herbivory contribute to the co-existence of genetically distinct populations of an herbivore, we investigate the interaction between honeysuckle (Lonicera periclymenum) and sympatric specialist and generalist populations of the spider mite Tetranychus urticae. Mite folivory induces the production of sticky droplets on honeysuckle, which have a defensive role: they increase mite mortality directly, and potentially indirectly by increasing the arrestment of a predator. Droplet induction depends on mite genotype, as well as the preference to feed on honeysuckle, where the generalist avoids this host and the specialist suppresses droplet production. These traits are heritable and dominant in F1 hybrids between generalists and specialists. Selection pressure from honeysuckle and differences in host preference likely reduce the opportunity of mating encounters on this host. We propose that the interplay between selection from host plant defences and ecological barriers to hybridization contribute to the persistence of genetically distinct populations of a single species in sympatry.